PENGARUH PENERIMAAN PAJAK, PMA DAN PMDN TERHADAP PERTUMBUHAN EKONOMI SUMATERA UTARA - Indah Dela Puspitasari, Seli; Theophilus Telaumbanua, Satrio; Mei Karina Nahampun, Britania; Uliarta Gultom, Christina; Angelina Sihotang, Rouli (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2024)
Economic growth is defined as a process of increasing output per capita in the long term. The purpose of this study was to determine the effect of tax revenue, Foreign Direct Investment (FDI), Domestic Direct Investment (DDI) on economic growth in North Sumatra. This study uses a quantitative approach using time series data sourced from the Central Bureau of Statistics (BPS) of North Sumatra in 2010-2022. Data analysis techniques using multiple regression analysis using the E-Views 10 program. The results found that tax revenue has a positive and insignificant effect on economic growth, Foreign Capital Receipts have a negative and significant effect on economic growth, while Domestic Capital Receipts have a negative and insignificant effect on economic growth.